ENCOURAGING STUDENT AUTONOMY THROUGH PROJECT-BASED LEARNING - Babaxanova Dildora Ikromjon qizi (European Science Publishing, 2025)
Project-Based Learning (PBL) is an instructional approach that fosters student autonomy by engaging learners in real-world, meaningful projects. This article explores the role of PBL in promoting self-directed learning, critical thinking, and motivation in English as a Foreign Language (EFL) classrooms. It examines strategies for implementing PBL effectively and discusses challenges that educators may encounter. The findings suggest that PBL enhances learner engagement, responsibility, and language proficiency by encouraging students to take ownership of their learning process.
Keywords: Project-Based Learning, Student Autonomy, Self-Directed Learning, EFL Teaching, Language Acquisition, Collaborative Learning, Motivation, Authentic Assessment.